A Review of Resettlement Management Experience in China Hydropower Projects : Identifying Key Lessons Learned - World Bank (World Bank, Washington, DC, 2020)
In China, as elsewhere, hydropower presents development practitioners with a dilemma. Hydropower holds the promise of relatively cheap, clean, and sustainable electrical power generation; and yet, it can also generate significant and complex environmental and social problems. A major challenge is striking a balance between potential development benefits and development-induced harms. This review summarizes the China hydropower resettlement experience as assessed by Chinese resettlement practitioners for the purpose of identifying lessons that may be applicable elsewhere. Of course, the China hydropower context includes unique or unusual aspects, and others would need to adapt China’s lessons to their own country or sector conditions. Nevertheless, for policymakers and practitioners interested in strengthening the efficiency and effectiveness of resettlement performance, at either the sectoral or single-project level, this review identifies practical steps they may find ready for consideration or use.